Power quality improvement using Distribution Static Synchronous Compensator. (March 2023) - Sah, Pranjali; Singh, B.K.
Highlights: Controllers of DBN and CNN were developed and simulated. Voltage swell as voltage were analyzed using DL controllers. D-STATCOM is constructed and simulated using MATLAB software. Proposed system provides better voltage enhancement. In future, by using smart metering it will be adapted in smart grid architecture. Abstract: A Power quality problem is an occurrence manifested as a nonstandard voltage, current or frequency that results in a failure or a mis-operation of end user equipments. Hence, the optimal advancement of power quality is concentrated by this proposed model with Deep Belief Nets (DBN) and Convolutional Neural Networks (CNN) utilizing Distribution Static Synchronous Compensator (DSTATCOM). Here, the major objective is that for the mitigation of current distortion, voltage enhancement, along with minimization of harmonics, the reactive power control in DSTATCOM is focused more by utilizing DBN with CNN. Utilizing the proposed Simulink design model of DSTATCOM, which is employed for enhancing the power quality in a distributed system, the aforementioned objective could be obtained. The simulations were performed using MATLAB SIMULINK. From the simulation result it is observed that the proposed framework have successfully accomplished harmonic substance and voltage profile enhancement. Graphical abstract: Image, graphical abstract